Pengembangan Sistem Informasi Sebagai Pusat Data Melalui Aplikasi PD-Seru di Dinas Pendidikan Kabupaten Gresik - Moch. Yafa Sultan Arkanu; Maysa Daliya; Sahudi, Sahudi; Husnul Laila (Program Studi Manajemen Pendidikan Islam, 2025)
The Gresik Regency Education Office faces challenges in managing education data that is still not integrated, not integrated, and based on manual documents. This causes inefficiencies in the process of collecting, verifying, and reporting data, and hinders the process of decision-making based on accurate and real-time data. This study discusses the development of an innovative information system that aims to be an effective data center through the implementation of the PD-SERU Application within the Gresik Regency Education Office. This research is a descriptive analytical study using a combination of observation and interview data collection techniques. The results show that the PD-SERU Application can improve accessibility, speed, and security in data management, making a positive contribution to the operational effectiveness of the Education Office. The development of the PD-SERU information system has proven effective in creating an integrated data center within the Gresik Regency Education Office. The implementation of this system has had a significant impact in the form of increased data accuracy, accelerated data collection and reporting processes, and work efficiency. The existence of PD-SERU is expected to become a foundation for making more data-based education policies and strategies in the future.